The Electrical Resistivity and Acoustic Emission Response Law and Damage Evolution of Limestone in Brazilian Split Test - Xinji Xu; Bin Liu; Shucai Li; Jie Song; Ming Li; Jie Mei (Advances in Materials Science and Engineering)
The Brazilian split test was performed on two groups of limestone samples with loading directions vertical and parallel to the bedding plane, and the response laws of the electrical resistivity and acoustic emission (AE) in the two loading modes were obtained. The test results showed that the Brazilian split test with loading directions vertical and parallel to the bedding showed obviously different results and anisotropic characteristics. On the basis of the response laws of the electrical resistivity and AE, the damage variables based on the electrical resistivity and AE properties were modified, and the evolution laws of the damage variables in the Brazilian split test with different loading directions were obtained. It was found that the damage evolution laws varied with the loading direction. Specifically, in the time-varying curve of the damage variable with the loading direction vertical to the bedding, the damage variable based on electrical resistivity properties showed an obvious damage weakening stage while that based on AE properties showed an abrupt increase under low load.